Human platelet lysate-derived extracellular vesicles enhance angiogenesis through miR-126 - Bordin, Antonella; Chirivì, Maila; Pagano, Francesca; Milan, Marika; Iuliano, Marco; Scaccia, Eleonora; Fortunato, Orazio; Mangino, Giorgio; Dhori, Xhulio; De Marinis, Elisabetta; D'Amico, Alessandra; Miglietta, Selenia; et al. (Cell proliferation, 2022)
Objectives Extracellular vesicles (EVs) are key biological mediators of several physiological functions within the cell microenvironment. Platelets are the most abundant source of EVs in the blood. Similarly, platelet lysate (PL), the best platelet derivative and angiogenic performer for regenerative purposes, is enriched of EVs, but their role is still too poorly discovered to be suitably exploited. Here, we explored the contribution of the EVs in PL, by investigating the angiogenic features extrapolated from that possessed by PL. Methods We tested angiogenic ability and molecular cargo in 3D bioprinted models and by RNA sequencing analysis of PL-derived EVs. Results A subset of small vesicles is highly represented in PL. The EVs do not retain aggregation ability, preserving a low redox state in human umbilical vein endothelial cells (HUVECs) and increasing the angiogenic tubularly-like structures in 3D endothelial bioprinted constructs. EVs resembled the miRNome profile of PL, mainly enriched with small RNAs and a high amount of miR-126, the most abundant angiogenic miRNA in platelets. The transfer of miR-126 by EVs in HUVEC after the in vitro inhibition of the endogenous form, restored angiogenesis, without involving VEGF as a downstream target in this system. Conclusion PL is a biological source of available EVs with angiogenic effects involving a miRNAs-based cargo. These properties can be exploited for targeted molecular/biological manipulation of PL, by potentially developing a product exclusively manufactured of EVs.